(untitled) (Research, Society and Development, 2020)
National Public Policy Conferences are considered important mechanisms of social participation in Brazil. Given the periodic realization of National Conferences on Food and Nutrition Security, the aim of this article is to investigate the contributions of conferences to the formation of an action arena in Food and Nutrition Security, based on the speech of social actors who participated in the trajectory of the conferences as integrant of the National Council of Food and Nutrition Security (CONSEA). Seven members and former CONSEA members were interviewed. The interviews were conducted, based on a semi-structured script, recorded and later transcribed. The thematic content analysis was used for data analysis and the results were grouped into four axes: general evaluation of the conferences; conferences and democracy; capacity of the conferences to influence policies and actions and challenges. Participants considered the conferences to be successful democratic events, contributing to the exercise and enhancement of democracy in Brazil, and influencing the elaboration of public policies. Existing challenges have also been reported, such as tensions and disagreements, which are partly due to misunderstandings related to the complexity of the theme. Its concluded that National Conferences on Food and Nutrition Security are space for building a social and political space, since they allow the recognition of actors and interests, consensuses and dissent.